2009
DOI: 10.1016/j.joca.2008.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Mevastatin reduces cartilage degradation in rabbit experimental osteoarthritis through inhibition of synovial inflammation

Abstract: During the development of experimental OA, intra-articular administration of HMG-CoA reductase inhibitor (statin) reduces inflammatory cell infiltration and matrix-degrading enzyme expression, thus limiting cartilage degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 45 publications
4
74
0
2
Order By: Relevance
“…This model induces instability of joint, resulting in typical OA-like lesions. The model is widely used in studies with pharmacological agents for OA [34,35]. Variable cartilage degeneration was detected in the present study, supporting the reliability and repeatability of the model.…”
Section: Discussionsupporting
confidence: 84%
“…This model induces instability of joint, resulting in typical OA-like lesions. The model is widely used in studies with pharmacological agents for OA [34,35]. Variable cartilage degeneration was detected in the present study, supporting the reliability and repeatability of the model.…”
Section: Discussionsupporting
confidence: 84%
“…We investigated the in vivo effects of baicalein on cartilage in experimental OA over a period of 6 weeks, which is similar to the durations used in previous studies [26,27]. We found that the cartilage displayed OA-like changes; Therefore, 6 weeks was sufficient to induce OA using ACLT.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have demonstrated that NF-κB triggers the expression of an array of genes that induce destruction of the articular joints, thereby leading to the onset and progression of OA. Interestingly, NF-κB has been reported to regulate the effects of IL-1β on the transcription of MMP-13 in human chondrocytes [26]. The anti-inflammatory capacity of KLF2 has been widely correlated to its inhibitory effects on the binding ability of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, multiple lines of evidence have shown that the atheroprotective effects and cholesterol-lowering abilities of statins are mediated by KLF2 [25]. Interestingly, mevastatin, a member of the statin family, has been proven to reduce inflammatory cell infiltration and cartilage degradation by suppressing the expression of IL-1β, MMP-3, and MMP-13 in rabbit synovial tissues [26]. In addition, KLF2 has been reported to be involved in the anti-inflammatory ability of montelukast, another licensed drug clinically used for the treatment of asthma [29].…”
Section: Discussionmentioning
confidence: 99%